Z-number based earned value management (ZEVM): A novel pragmatic contribution towards a possibilistic cost-duration assessment. (May 2020) - Hendiani, Sepehr; Bagherpour, Morteza; Mahmoudi, Amin; Liao, Huchang
Highlights: We propose a possibilistic EVM to control the deviations of cost-duration of activities and total project. The concept of z-numbers is utilized to model EVM by considering subjective possibilities. Utilization of the proposed framework for solving an illustrative case explored. Implications for project managers and end-users are presented. Abstract: The Earned value management (EVM) is one of the simplified analytical cost-duration assessment tools which assist project managers in monitoring the status of the project undertaken. The EVM has been elaborated by both deterministic and uncertain numbers such as fuzzy logic in the light of time. Even though cost-duration analysis is so sensitive and fluctuating in projects, the adopted approaches were unable to consider the conspicuous unreliability which is always involving the decision-making data. This problem impedes project managers to trust the foreseen inferences. To help in overcoming this critical deficiency, Z-numbers were proposed to take possibilities and reliabilities into account. Applying Z-numbers and possibilistic modeling in the EVM is a challenging topic which causes the accuracy of cost-duration tracing results to be significantly enhanced. This paper presents the application of z-numbers for modeling the earned value indicators and proves the superiority of the ZEVM against traditional fuzzy EVM. This work originally adds to the state-of-the-art literature on earned value management by presenting a proposal and applications of a new as Z-Earned Value Management (ZEVM). An illustrative case is resolved to magnify the capability of the proposed framework in dealing with higher levels of uncertainty associated with decision-making data.